PENGARUH DISIPLIN TERHADAP KINERJA PEGAWAI BAGIAN KEPEGAWAIAN PADA KANTOR KECAMATAN BATURAJA BARAT OGAN KOMRING ULU - Christianti, Christianti; Mardeli, Iis (JMBI (Journal of Marketing and Business Intelligence), 2024)
The availability of quality human resources and having a high work ethic is the main capital of an organization to be able to be on par with other organizations. The problem faced is how discipline affects the performance of Personnel Division Employees of the Personnel Division of the Baturaja Barat Ogan Komering Ulu District Office. The purpose of this study is to determine the effect of discipline on the performance of Personnel Division Employees of the Baturaja Barat Ogan Komering Ulu District Office and is useful as a reference for further research on discipline and employee performance. The hypothesis proposed, Discipline has a positive effect on the performance of Personnel Division Employees of the Baturaja Barat Ogan Komering Ulu District Office. From the results of the discussion, the correlation between discipline in efforts to improve the performance of Personnel Division Employees of the Baturaja Barat Ogan Komering Ulu District Office obtained an r figure of 0.57. After consulting with conservative standards, it lies between 0.400-0.599 which is included in the moderate correlation. So it can be said that there is a moderate influence between discipline and the performance of the Personnel Division Employees of the West Baturaja District Office, Ogan Komering Ulu.